Highly Diastereoselective 1,6-Conjugate Addition of Arylboronic Acids to Securinine - Perez, Marc; Ayad, Tahar; Maillos, Philippe; Poughon, Valérie; Fahy, Jacques; Ratovelomanana-Vidal, Virginie (Synlett, 2016)
The asymmetric 1,6-conjugate addition of arylboronic acids to natural securinine under rhodium(I) catalysis displays a very high regioselectivity, along with a remarkable diastereoselectivity (>99:1) and high yields. The in vitro cytotoxicity of the resulting securinine analogues was assayed against HCT-116 colon cancer cells, giving a new insight into the structure–activity relationship of securinine.
Keywords: catalysis; rhodium; securinine; arylboronic acids; conjugate addition; medicinal chemistry